2017
DOI: 10.1155/2017/4210867
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Promotes Neural Differentiation of Rat Adipose Tissue-Derived Stromal Cells through Wnt/β-Catenin Signaling Pathway

Abstract: Adipose tissue-derived stromal cells (ADSCs) are a high-yield source of pluripotent stem cells for use in cell-based therapies. We explored the effect of andrographolide (ANDRO, one of the ingredients of the medicinal herb extract) on the neural differentiation of rat ADSCs and associated molecular mechanisms. We observed that rat ADSCs were small and spindle-shaped and expressed multiple stem cell markers including nestin. They were multipotent as evidenced by adipogenic, osteogenic, chondrogenic, and neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Both Wnt3a, ANDRO and Li are able to turn on the Wnt canonical pathway, constituting a potentially relevant therapeutic approach to up-regulate Wnt canonical signaling in vivo. Indeed, both molecules promote the accumulation of b-catenin by preventing the degradation of this protein through the inhibition of GSK-3b (Toledo and Inestrosa 2010;Tapia-rojas et al 2015;Liang et al 2017;Xia et al 2017;Rivera et al 2018). Relevantly, the canonical Wnt signaling has emerged as one of the more relevant pathways to be addressed when approaching to neurodegenerative disorders, overall because it has been related to several brain pathologies, such as AD, autism, schizophrenia and Parkinson disease.…”
Section: Discussionmentioning
confidence: 99%
“…Both Wnt3a, ANDRO and Li are able to turn on the Wnt canonical pathway, constituting a potentially relevant therapeutic approach to up-regulate Wnt canonical signaling in vivo. Indeed, both molecules promote the accumulation of b-catenin by preventing the degradation of this protein through the inhibition of GSK-3b (Toledo and Inestrosa 2010;Tapia-rojas et al 2015;Liang et al 2017;Xia et al 2017;Rivera et al 2018). Relevantly, the canonical Wnt signaling has emerged as one of the more relevant pathways to be addressed when approaching to neurodegenerative disorders, overall because it has been related to several brain pathologies, such as AD, autism, schizophrenia and Parkinson disease.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that Andro can stimulate neurogenesis in the adult hippocampus 13. Liang et al found that Andro may exhibit neuroprotective effects in nervous system diseases 14. Meanwhile, a recent study showed that Andro exerted strong neuroprotective effects in a mouse model of Parkinson’s disease 15.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, ANDRO (5–100 μ g/kg, i.p.) increased Wnt/ β -catenin signaling as evidenced by the enhanced nuclear β -catenin expression and inhibited GSK-3 β (pSer9) [ 70 ].…”
Section: The Neurobiological Role Of Andrographolide: Molecular Mecha...mentioning
confidence: 99%
“…Furthermore, NOX2 and iNOS expression were reduced by impairing PI3K/protein kinase B-(AKT-) dependent NF-κB and HIF-1α activation in cerebral ischemia in mice [24]. [20], [44], [47], [26], [46]) 22], [94], [95], [52], [50], [51], [55], [56], [57], [54]) 16], [62], [61], [63], [57], [96]) [27], [68], [69], [97], [70])…”
Section: Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation